Digitization of Subsidized Fertilizer Distribution and Operational Challenges in Serving Aging Farmers: A Systematic Literature Review - Salsabila, Norisa; Nugraha, Hari Susanta; Wijayanto, Andi (Jurnal Ragam Pengabdian, 2026)
Digitalization plays a role as a thing that moves in modern service management. Digitalization is not only used for administrative work needs, but also for the process of restructuring operations, optimizing information circulation, improving data accuracy, and strengthening accountability mechanisms. The purpose of this study is to see how digitalization in agriculture is able to serve elderly farmers in the subsidized fertilizer scenario. This research method uses the systematic literature review method with PRISMA logic. Data was obtained from articles published from 2021-2026 with a total of 17 articles. The results of this study are that the use of technology or digitalization in the agricultural sector has obstacles in its skills for elderly farmers such as low digital literacy and difficulties in accessing technology. This research proposes to build inclusive technology in four dimensions, including system readiness to ensure easy access to digitalization for elderly farmers.